2002
DOI: 10.1183/09031936.02.00273502
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and oral contribution to inhaled and exhaled nitric oxide: a study in tracheotomized patients

Abstract: Nitric oxide (NO) is produced at different sites in the human airways and may have several physiological effects. Orally-produced NO seems to contribute to the levels found in exhaled air. Autoinhalation of nasal NO increases oxygenation and reduces pulmonary artery pressure in humans. The aim of this study was to measure the concentration and output of NO during nasal, oral and tracheal controlled exhalation and inhalation.Ten tracheotomized patients and seven healthy subjects were studied. The mean ¡ SEM fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
1
33
1
1
Order By: Relevance
“…There is a mandatory external quality control (QC) Procedure for NIOX MINO that includes a Daily QC and a Full QC. The nNO levels are considerably higher than lower airway levels [23,24]. In contrast to the lower airways, nNO levels in patients with upper airway inflammation are rather decreased than increased when compared with healthy controls [25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…There is a mandatory external quality control (QC) Procedure for NIOX MINO that includes a Daily QC and a Full QC. The nNO levels are considerably higher than lower airway levels [23,24]. In contrast to the lower airways, nNO levels in patients with upper airway inflammation are rather decreased than increased when compared with healthy controls [25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…It is, however, important to note that this assumption may only be true under the exact conditions of this study. For example, at a different flow rate the relative contribution from the sinuses and nose may differ and the sinus contribution seems to be larger during inhalation compared to exhalation [23]. Nevertheless, using the methods described here, it may be possible to better separate sinus NO from nasal mucosal NO release.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that oral NO production exists and is dependent on intake of nitrate, which is reduced to nitrite and further to NO by bacteria in the oral cavity [24]. Recently, the authors observed that the oral cavity and oropharynx contributes to approximately half of the NO levels in orally exhaled air, shown by measuring NO production from tracheotomised patients [25]. The authors therefore cannot disregard the fact that the increase in oral eNO after endotoxin challenge derives from NO produced in the mouth.…”
Section: Discussionmentioning
confidence: 99%